Persepsi Auditor Indonesia: Artificial Intelligence dan Dampaknya yang Mengubah Kualitas Audit - Hotma Glorya Ika Sari; Daniel Artha Wahyuda (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to examine Indonesian auditors' perceptions regarding the use of artificial intelligence (AI) in the audit process and its impact on audit quality. The study population comprises auditors employed at Public Accounting Firms in the JABODETABEK area. A purposive sampling technique was employed, resulting in a total sample of 208 auditors. This research utilizes a survey method through a questionnaire that includes items measuring the perceived ease of use and perceived usefulness of three types of AI systems: Assisted, Augmented, and Autonomous. The findings reveal that Assisted AI Systems are perceived as the easiest to use and the most beneficial, followed by Augmented AI Systems, which are considered more complex. In contrast, Autonomous AI Systems are regarded as the most challenging to use and the least advantageous. These results indicate significant differences in auditors' perceptions of the three AI system types, underscoring the importance of selecting appropriate technologies to enhance audit efficiency and quality. This study provides valuable insights for audit organizations in optimizing AI implementation while enhancing auditors' competencies to navigate challenges in the digital era.